The Influence of Financial Performance on Stock Returns: A Case Study of Retail Companies Listed on the Indonesia Stock Exchange (2015-2022) - Hasanudin Hasanudin (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
Financial performance can have an impact on the financial activities of an entity, be it a company, organization or individual. Financial performance is a description of an entity's financial position that is examined using financial analysis techniques to determine the entity's good and bad financial conditions, which are indicative of work performance during a specific time period. This research aims to analyze the influence of the variables Earning Per Share (EPS), Return On Equity (ROE), Debt To Equity Ratio (DER), and Price Earning Ratio (PER) on the performance of stock returns in retail trading sector companies listed on the Stock Exchange of Indonesia. This research uses quantitative methods with the Hausman test, Chow test and data analysis using the classical assumption test. Research data was obtained from the official website of retail trade sector company financial reports during the 2015-2022 period with a sample of 12 companies from a population of 32 companies. The results of the research found that individually, Earning Per Share, Return On Equity, Debt To Equity Ratio, and Price Earning Ratio had a positive and significant influence on Stock Returns.